Development a Modification Factor for Lugeon's Water Pressure Test Based on the Intersect Angle Between Borehole and Rock Mass Discontinuities - Ganjalipour, Kamal; Esmaeilzadeh, Masoud (Geotechnical and geological engineering, 2021)
Lugeon test or water pressure test is used by engineers usually for determining the in-situ permeability in most geotechnical projects. Since 1933, this test has been used with the least possible modification. Some researchers have been trying to interpret the results of this test, including Ewert (Dam Eng 8(2):343–352, 1997) and Foyo et al. (Eng Geol 77(1):69–82, 2005). For example, Foyo introduced the secondary permeability index, but he did not change the general principals of the test method. In this study, it has been attempted to make some modifications in the results obtained from the Lugeon test in order to achieve more accuracy. In most geotechnical projects, in order to achieve a general impression of permeability, they usually drill several boreholes having diverse dip angles for executive, technical and scientific reasons. If the geological characteristics and joint features of the area would be similar, the adjustment in drilling angle of boreholes will lead to change the contact length of the discontinuities with the borehole wall. The authors believe the changes in contact length of the discontinuities in borehole walls lead to a change in Lugeon test results; therefore, they studied it using several various numerical models. The results showed that by decreasing the angle between the borehole and joint, inlet flow to the joint increases, and in turn, this increase is related with the contact length of joint with the borehole wall. Accordingly, the authors developed a correction factors to eliminate the effect of changes of drilling angle of the borehole based on the results of Lugeon test. Also, the results of showed that the nature of the Lugeon test under water table is very different with the Lugeon test above it, due to the hydrostatic pressure.